Sociological Characteristic of Drug Users in Grass-Root Areas of Isfahan (Drug Control Headquarters, Research and Education Office, 2004)
The present research is based on this question: "Is there any relationship between the type of used drug and the method of drug consumption with the motivation and view of drug users?" After reviewing various assumptions, the author concludes that one must consider the type of used drug, the method of consumption and even the motivation of drug use in applied categorization of addicts. The author believes that no mechanism for fighting against drug addiction phenomenon will success unless we consider the background of the addict, the type of used drug and the method of drug consumption (lifetime or recreational).